Editorial | TIM RaDar as a Practical Screening Tool for IMRaD Articles: Consensual Publication Standards Among Indonesian Psychological Journal Editors [TIM RaDar Sebagai Alat Screening Praktis untuk Artikel IMRaD: Standar Publikasi Konsensual] - Edwin Adrianta Surijah; Juneman Abraham; Christiany Suwartono; Ide Bagus Siaputra (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2021)
TIM RaDaR is an initiative to discover common standards for scientific publications in the field of psychology in Indonesia. Through this standard, authors (i.e., researchers, students, or lecturers) may prepare their manuscripts to meet the basic criteria for scientific publication. The writing criteria comprise of Title, Introduction, Methods, Results and Discussion, and References. This article also provides a checklist to aid authors and journal editors in evaluating manuscripts to be published. As an initiative, this article aims to become a starting point in synergizing better quality scientific publications in the field of psychology in Indonesia. TIM RaDaR adalah sebuah inisiatif untuk menggali standar bersama publikasi ilmiah psikologi Indonesia. Melalui standar ini, penulis (peneliti, mahasiswa, atau dosen) dapat mempersiapkan tulisan yang mereka susun untuk memenuhi kriteria dasar publikasi ilmiah. Kriteria tersebut mencakup penulisan Judul, Pendahuluan, Metode, Hasil dan Diskusi, serta Pustaka Acuan (Title, Introduction, Methods, Results and Discussion, and References). Tulisan ini juga memberikan sebuah checklist yang dapat digunakan sebagai alat bantu bagi penulis dan pengelola jurnal untuk mengevaluasi tulisan yang telah disusun. Sebagai suatu inisiatif, tulisan ini menjadi titik awal sinergi publikasi ilmiah psikologi Indonesia yang lebih bermutu di masa mendatang.